Juggling Risks: Towards a Safe and Inclusive Work Environment for Pregnant Soldiers in the Danish Army - Christine Svop (Scandinavian Military Studies, 2021)
This article investigates the negative experience of pregnant soldiers. Drawing on seven interviews with female officers pregnant during their service in the Danish army, the article shows how, obliged to prioritise between the welfare of their unborn child and themselves on one hand and, on the other, the physically demanding performance of the military role model leading by example in the successful execution of their duties, these officers find it difficult reconciling the role of mother-to-be and the role of soldier. The pregnant body offers a challenge to the pregnant officer’s performance as a disciplined and physically able soldier, it is argued; this, in turn, challenges the pregnant officer’s social identity as soldier and leader. The article offers evidence that prevailing gender biases present difficulties for pregnant soldiers seeking to successfully navigate the demands of their work life. As leaders in the army seem to overlook these challenges, the two principal purposed of the article are as follows: First, to spell out the need to better support serving mothers-to-be through the enforcement of a pregnancy policy intented to secure a healthy work environment. Second, that if we are to secure equal opportunities for men and women in the armed forces, equity must be achieved through strategies of gender mainstreaming. However, a change in the work culture of the army is needed to make equity socially acceptable. These purposes will be supported by reference to the case study of pregnant soldiers.